PEMBERDAYAAN PERPUSTAKAAN PESANTREN BERBASIS OTOMASI DAN DIGITAL - Mahmud, Muhammad Amir (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2013)
Library is one means a place to get information.Today many libraries are still not maximized utilization. This is due to several factors, including the old paradigm that sees the library just as